Screening for depression in chronic haemodialysis patients as a part of care in dialysis setting: a cross-sectional study - Kubanek, Alicja; Renke, Marcin; Godlewska, Beata R.; Paul, Przemysław; Przybylak, Mateusz; Kowalska, Anna S.; Wąż, Piotr; Błaszczyk, Michał; Macul-Sanewska, Aleksandra; Rutkowski, Przemysław; Czarnacka, Kamila; Bednarski, Krzysztof; et al. (Frontiers in Psychiatry, 2024)
Background Depressive disorder is common among haemodialysis patients. The purpose of this study was to explore approaches to diagnosing depression in the context of a real-life setting, with the view of creating practical recommendations. It also aimed to evaluate the prevalence of depression and dementia. Methods We conducted a cross-sectional study in two Dialysis Centres in Poland. Cognitive functions were evaluated using Mini–Mental State Examination (MMSE). The screening for depressive symptoms was assessed using Beck Depression Inventory II (BDI-II). The diagnosis of major depressive disorder was confirmed by a psychiatrist using Diagnostic and Statistical Manual of Mental Disorders 5 (DSM-5). Sociodemographic and clinical data were also collected. Results Initially, 136 patients agreed to participate in the study. Dementia was found in 13% of the study group. Sixty-two patients did not agree to perform all the proposed tests and were not included in the analysis, which eventually consisted of 70 patients. According to BDI-II, depressive symptoms were present in 35.7% of patients, while the diagnosis of major depressive disorder (MDD) was confirmed by the psychiatrist in 25.7%. According to the ROC analysis the optimal cut-off score for diagnosing MDD using BDI-II was ≥13 points. Conclusions This study suggests that the regular screening for depressive symptoms, followed by a psychiatric consultation in selected patients, might improve diagnosing depression with the goal of achieving a higher quality of life and a lower mortality rate. It may also be a cost-effective model for the management of depression among the haemodialysis population.